2017
DOI: 10.1194/jlr.m070730
|View full text |Cite
|
Sign up to set email alerts
|

Preferential hydrolysis of truncated oxidized glycerophospholipids by lysosomal phospholipase A2

Abstract: generation and elimination of ROS affects cellular structure and function. Within lipid membranes and particles, unsaturated and polyunsaturated acyl groups conjugated at the sn-2 position of phospholipids (PLs) are susceptible to ROS inducing nonenzymatic fragmentation of the unsaturated acyl chains. As a result, various truncated oxidized glycerophospholipids (ox-PLs) are formed with an oxidized short or medium chain terminating in an aldehyde or carboxylic acid at the sn-2 position (2). The truncated ox-PLs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Similar to the findings of Podrez et al ( 70 ), we found micromolar levels of OxPL species in murine whole blood, and a significant increase in response to high-fat feeding. As has been previously reported, HFD feeding induces PLA2 activity in blood ( 71 ) and it has been found that PLA2 preferentially cleaves the sn -2 moiety from truncated OxPL ( 72 ), offering an explanation for the increased level of LysoPC at the cost of carbonyl-PC species. Additionally, it was previously demonstrated that during obesity adipocytes significantly up-regulate two isoforms of secretory PLA2, specifically PLA2G5 and PLA2G2E ( 73 ).…”
Section: Discussionmentioning
confidence: 62%
“…Similar to the findings of Podrez et al ( 70 ), we found micromolar levels of OxPL species in murine whole blood, and a significant increase in response to high-fat feeding. As has been previously reported, HFD feeding induces PLA2 activity in blood ( 71 ) and it has been found that PLA2 preferentially cleaves the sn -2 moiety from truncated OxPL ( 72 ), offering an explanation for the increased level of LysoPC at the cost of carbonyl-PC species. Additionally, it was previously demonstrated that during obesity adipocytes significantly up-regulate two isoforms of secretory PLA2, specifically PLA2G5 and PLA2G2E ( 73 ).…”
Section: Discussionmentioning
confidence: 62%
“…Our demonstration of elevated amounts of the oxidized phospholipids PAzPC and SAzPC in Atg7 f/f Tyr-Cre brains indicates that the turnover of these substances is altered. The differential effects of autophagy inhibition on different classes of oxidized phospholipids (PAzPC and SAzPC versus Lyso-PPC, Lyso-SPC, PLPC, and SLPC in the Atg7 f/f Tyr-Cre brain), which are similar to those observed in Atg7 f/f K14-Cre skin cells [ 58 ], may be caused by the delivery of substrates to lysosomal phospholipase A2 [ 59 ]. Augmentation of oxidatively modified phospholipids in cellular membranes affects their polarity and permeability, which has been specifically demonstrated for PLPC-derived PazPC [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we found that LPLA2 preferentially hydrolyzed truncated OxPCs in vitro. 11 This study also showed that LPLA2-overexpressed CHO cells more efficiently catabolize PAzPC in the cultured system than CHO cells. To determine whether LPLA2 is connected with the metabolic pathway of truncated OxPCs by AMs, mouse AMs were prepared from both wild-type and LPLA2 deficient C57BL6 mice Alveolar macrophages of LPLA2 deficient mice develop phospholipidosis due to the reduction of phospholipid digestion.…”
Section: Removal Of Truncated Oxpc By Ams Prepared From Wild-type or mentioning
confidence: 54%